Star‐Shaped Macromolecules with the Core of Hexakis‐(fluoren‐2‐yl)benzene and the Periphery of Pyridine: Synthesis and Application as Solution‐Processable Electron‐Transport Materials. Issue 18 (14th July 2015) - Yin, Xiaojun; Miao, Jingsheng; Xiang, Yepeng; Wu, Hongbing; Cao, Yong; Yang, Chuluo
<x xml:space="preserve">Abstract</x> Three new star‐shaped macromolecules with hexakis(fluoren‐2‐yl)benzene as the core and pyridine as the periphery (2Py‐HFB, 3Py‐HFB, and 4Py‐HFB) are synthesized and characterized. The synthetic conditions of octacarbonyldicobat‐catalyzed cycloaddition reaction for different alkyne precursors are investigated. The coordination interaction between the pyridine ring of alkyne precursor and the cobalt catalyst may result in very low yield of the cyclotrimerization product. However, with the increase of the catalyst loading, the yields of the intermediates of cyclopentadienone are enhanced. Then, the desired cyclotrimerization products can be obtained by the Diels–Alder reactions of cyclopentadienone with acetylene in good yield. These new compounds exhibit good thermal stability and favorable electron affinity. By using the new compounds as electron‐transporting materials, all‐solution‐processed phosphorescent organic light‐emitting devices (OLEDs) show good performance with a maximum current efficiency of 5.6 cd A−1 and maximum external quantum efficiency of 4.68%.